2012
DOI: 10.4236/jdm.2012.21012
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of the peripheral and central auditory pathway in patients with type 1 diabetes mellitus

Abstract: Although auditory alterations are not a typical symptom of diabetes mellitus (DM), they can occur in patients with type 1 DM. The findings of previous studies are controversial, because the frequency and degree of hearing loss varies, and quite often alterations are still subclinical. The typical test used to detect and manage hearing loss is the audiogram, but this test alone is only capable of detecting alterations due to injury of the inner hair cells and/or alterations in the central auditory pathway. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…It is observed that the TEOAE recordings are not very frequency selective as compared to DPOAE. 10,11 In the present study, mean DPOAE SNR values for diabetics were lower in all frequencies [2000, 3000, 4000, 5000 and 6000 Hz] for diabetics. An early onset high frequency cochlear dysfunction in diabetics was indicated by lower SNR values with significant decrease for 4, 5 and 6 kHz.…”
Section: Discussionmentioning
confidence: 75%
“…It is observed that the TEOAE recordings are not very frequency selective as compared to DPOAE. 10,11 In the present study, mean DPOAE SNR values for diabetics were lower in all frequencies [2000, 3000, 4000, 5000 and 6000 Hz] for diabetics. An early onset high frequency cochlear dysfunction in diabetics was indicated by lower SNR values with significant decrease for 4, 5 and 6 kHz.…”
Section: Discussionmentioning
confidence: 75%
“…Subclinical auditory alterations can only be detected with electrophysiological auditory tests – otoacoustic emission (OAE) and auditory brainstem response (ABR). Sensorial alterations can be distinguished with the OAE test, and neural alterations can be distinguished with the ABR test, which evaluates the auditory nerve and brainstem structures .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, T1DM may compromise the physiology of the inner ear at a subclinical level. In a previous literature review study, we investigated otoacoustic emissions, and a reduced amplitude was seen in patients with T1DM ( 18 ) . Histopathological findings of the inner ear of individuals with T1DM also favor this hypothesis, because they demonstrate the thickening of the capillary walls of the stria vascularis , the presence of hemorrhage and endolymphatic hydrops, a decreased number of fibers of the spiral blade, degenerative changes in the organ of Corti, and a reduction in external hair cells ( 3 ) .…”
Section: Discussionmentioning
confidence: 99%